The burden of ocular diseases in an underdeveloped village in Southwest Sumba, Eastern Indonesia, 2016 (Medical Journal of Indonesia, 2017)
Background: Prevalence estimates of ocular diseases in a given district are important to plan the programs of eye care services. This study aimed to describe the burden of ocular diseases as an initial step in improving eye care services in underdeveloped areas in Indonesia.Methods: A cross-sectional study was performed among residents of Perobatang Village in Southwest Sumba district in July 2016. Eye examinations were conducted by ophthalmologists, and visual acuity was measured by optometrists. Participants were provided with appropriate treatment according to diagnosis. Surgical services were offered two months after the examination.Results: After eximining a total of 667 of 1,459 (46%) residents, the result showed that the most frequent ocular problems were presbyopia (30.8%), cataract (12.8%), refractive error (11.3%), and pterygium (10.7%). The proportion of myopia was 5.9%, hyperopia was 5.0%, and astigmatism was 2.2%. Moreover, the proportion of blindness was 10%. Cataract caused blindness in 44 participants. Other causes of blindness included age-related macular degeneration, retinopathy, optic atrophy, glaucoma, retinal detachment and trauma.Conclusion: The burden of ocular problems in Perobatang Village, Southwest Sumba, Eastern Indonesia was high. These findings showed the importance of public health action from local government and non-governmental organizations to improve eye care services in Southwest Sumba district.